2012
DOI: 10.1523/jneurosci.3340-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fear by Learned Safety Signals: A Mini-Symposium Review

Abstract: Safety signals are learned cues that predict the non-occurrence of an aversive event. As such, safety signals are potent inhibitors of fear and stress responses. Investigations of safety signal learning have increased over the last few years due in part to the finding that traumatized persons are unable to utilize safety cues to inhibit fear, making it a clinically relevant phenotype. The goal of this review is to present recent advances relating to the neural and behavioral mechanisms of safety learning and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(139 citation statements)
references
References 81 publications
4
135
0
Order By: Relevance
“…Our rodent model safety signal conforms to safety-signal mechanisms involving modulation of BLA activity to reduce behavioral and physiological responses to stressors (30,31,34). Our findings suggest that the mechanism underlying the complex interplay between infant trauma-linked cues and later-life depressive-like behavior involves an amygdala 5-HT/CORT interaction that positively modulates the neurobehavioral dysregulation stemming from early-life trauma (Fig.…”
Section: Mechanisms Underlying Modulation Of Adult Neurobehavioral Fusupporting
confidence: 62%
See 2 more Smart Citations
“…Our rodent model safety signal conforms to safety-signal mechanisms involving modulation of BLA activity to reduce behavioral and physiological responses to stressors (30,31,34). Our findings suggest that the mechanism underlying the complex interplay between infant trauma-linked cues and later-life depressive-like behavior involves an amygdala 5-HT/CORT interaction that positively modulates the neurobehavioral dysregulation stemming from early-life trauma (Fig.…”
Section: Mechanisms Underlying Modulation Of Adult Neurobehavioral Fusupporting
confidence: 62%
“…The amygdala is a principal target of safety signals (35,37), which inhibit amygdala output to provide relief from fearful states (30,34,38).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Lesions of the posterior (i.e., parietal) insular cortex impair fear learning as measured by fear potentiated startle (Shi and Davis 1999) but not when measured via freezing (Lanuza et al 2004), whereas lesions of the anterior insular, that encompassed the RAIC, significantly augment fear learning when assessed via freezing (Lacroix et al 2000). More recently, lesions of the posterior insular region reduced the anxiety-relieving properties of a safety signal (Christianson et al 2011(Christianson et al , 2012. In these experiments, the group differences in pMAPK-IR and also the effects of PD098059 infusion were largest during counterconditioning, as opposed to normal fear conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…However, typically when cues are repeatedly paired with unconditioned aversive stimuli, they are avoided or the cue itself starts to induce fear or anxiety responses (Maren and Quirk, 2004;Thielen and Shekhar, 2002). As the presence of the FP reduces anxiety-like behavior, the partner rat may be acting as a safety cue, in which case SFiA could be considered a form of safety learning (Christianson et al, 2012). In support of this concept, it was observed that the context during the repeated exposures to a conspecific determined the extent to which anxiolysis would result upon subsequent exposures.…”
Section: Social Familiarity and Safety Cuesmentioning
confidence: 99%